Physics of solid surfaces, 1984 : proceedings of the Third Symposium on Surface Physics, Smolenice Castle, Czechoslovakia, 3-7 September 1984 - Koukal, J. (Jan) (Studies in surface science and catalysis, 1985)
In the last decade the scientific community has shown a great renewal of interest in the study of phenomena on solid surfaces. Developments in recent years have improved the level of understanding of solid surfaces, in terms of the detailed knowledge of electronic properties, surface crystalography, dynamics of gas-solid interactions, transport properties of both clean surfaces and surfaces with adsorbed species. This book contains the proceedings of the symposium which was attended by 100 scientists from 13 countries. The symposium covered important developments in theoretical and experimental studies of solid surfaces and interfaces. Thirteen invited lectures and 44 papers presented as short communications or posters made up the programme for the meeting. From the vast field covered by the symposium title, special attention was devoted to electronic structure of surfaces and interfaces, angle-resolved photoemission studies of solid surfaces, study of surface reactions and surface melting, and geometrical structure and dynamical processes at surfaces. The book is primarily directed to the surface physicists and chemists but also of interest to chemical physicists and catalysis researchers.